Perancangan Mebel Multifungsi Untuk Dormitory Mahasiswa Desain - Melisa Wiliaury; Adi Santosa; Grace Setiati Kattu (Intra, 2015)
Dormitory, or sometimes called hostel is some kind of temporary living space which is intended for a group of people, that commonly consists of schoolboys/girls and university students. The dorm room has a limited space and is unable to accommodate their activities, especially design students with their tasks. The complexity of the student's activity has to be accommodated in the dorm room which is their private space. Therefore, a multi-functional furniture design with a compact and flexible nature is needed to solve the user's problem.This design can be fulfilled with holding surveys and collecting literature data about dormitory, multi-functional furniture, and student activities as the user. The goal of this design is to study and understand that the student's complex activities can be accommodated by a single multi-functional furniture.